Consequences of vitamin B12 deficiency in infants of vegetarian mothers: a review (Research, Society and Development, 2022)
Objective: The present study aimed to analyze vitamin B12 deficiency in vegetarian breastfeeding women and its consequences for the mother-child binomial. Methodology: Bibliographic review article, with a search performed in PubMed, Scientifc Electronic Libraly Online and Google Scholar databases from 2013 to 2022. Health Descriptors were used: “Deficiency”, “Vitamin B12”, “Infants”, "Pregnancy". Original articles that were indexed in the selected databases, in the languages: Portuguese, English and Spanish, published in the last ten years (2013 to 2022), original articles, field studies and case reports were included. The exclusion criteria were articles that were not within the selected periodicity, non-original articles and articles that did not address the theme. Initially, 2535 articles were found, which after applying the inclusion and exclusion criteria, at the end of the search, 9 articles remained. Results: In the analyzed studies, it was evidenced that vitamin B12 deficiency can bring serious risks to the health of the mother-child binomial resulting in malformation of the central nervous system, failure in growth, developmental regression, hypotonia, difficulties in feeding, hyperirritability, apathy , weakness, drowsiness, low weight and height gain, which may affect the infant's cognitive development. Conclusion: When adopting a vegetarian diet, care must be taken with their food intake to avoid nutritional deficiencies and, therefore, adequate nutritional monitoring is necessary, so that this style of eating and life does not bring harm to maternal-childish health.